Chapter 9 Protestant place, Protestant props in the plays of Nicholas Grimald - Dutton, Elisabeth (Manchester University Press, 2020)
Elisabeth Dutton focuses on how Reformation Protestant writers asserted the historicity of scriptural events. She asks a crucial question: How do the Protestant playwrights manage to create any form of 'scene' by which their audiences might be able to situate themselves in these events? Dutton argues that to encourage these audiences, these playwrights - specifically John Bale, John Foxe, and Nicholas Grimald - used the accessible, physical reality of props to thereby overcome the challenges of presenting a Protestant history.